Empowerment of Student as An Agent of Change in the Prevention of COVID-19 Transmission in Annysa Elementary School, Tanjung Gusta, Deli Serdang District - Keloko, Alam Bakti; Rochadi, R. Kintoko (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease caused by the Sars-CoV-2 virus. As of 26 October 2020, Indonesia has reported 389,712 confirmed cases of COVID-19 and North Sumatra is included in it. Therefore this service has the aim of empowering school children in CTPS and making school children as agents of change to prevent COVID-19 in the surrounding environment, increasing the knowledge and attitudes of school children in CTPS to prevent COVID-19, empowering school children to become agents of change in prevent COVID-19 in the environment, especially families, and provide hand washing facilities equipped with soap. Activities that have been carried out are school socialization by providing explanations about empowering children as agents of change in breaking the chain of transmission of the COVID-19 disease, the practice of washing hands with soap according to the steps that have been set, and making Hand Sanitizers easily and safely so that they can be made. by students themselves at home as a step to prevent COVID-19. It is hoped that the school can continue to study its students, measure hands properly, and pay attention to the facilities that have been provided.